Is Grammar Instruction Acceptable in a Communicative Language Acquisition Course? - Duyvene de Wit, Helene E (South African Journal of African Languages, 1995)
Extreme approaches to grammar instruction may range from a grammar-based syllabus to a complete disregard of grammar, leaving the place of grammar instruction within a communicative approach unclear. The advantages & disadvantages of both extremes, the history of grammar instruction, & a study of automatization are addressed. Various approaches, including the traditional grammar translation method, the direct method, structuralism & audio-lingualism, transformational-generative grammar, & the communicative approach are discussed. It is argued that grammar teaching & a communicative approach are mutually supportive. Some suggestions are offered regarding the teaching of grammar in African languages. 10 Figures, 63 References. Adapted from the source document